Effects of phytogenic products on gut morpho-histology of broiler chickens - Megaache Mounia; Alloui Nadir; Bennoune Omar (International Journal of Veterinary Science and Research - Peertechz Publications, 2018)
The objective of this experimental survey is to distinguish the effect of phytogenic products (Volarom®) as an alternative to antibiotic growth promoters (AGP) on the gut morpho-histology of broilers chickens, reared under optimal environmental conditions. Undred 1-day- Cobb strain chick males were divided into 2 groups (control and experimental). The broiler chickens received the following feed: control group: basic feed, experimental group: basic feed + 50 ml of phytogenic complex / 50 chicks in water for 42 days. At the age of 42 days, five birds per treatment were randomly selected and slaughtered. Representative segments of the gut broiler chickens (duodenum, jejunum and ileum) were removed from each  slaughtered bird and then subjected to fixation and histological observation. Ten consecutive villi were analyzed, measuring their height and depth. Height was measured from the base of the villi at the junction of the crypt to the tip of the villi. For morphometry the software "Image J1-45s" was used Version 1.6.0_20. The gut morpho-histological structure of broiler chickens results indicated that the addition of 50 ml of phytogenic products / 50 chicks in water for 42 days decreased respectively the villi height of the duodenum, jejunum and ileum (1230 μm ± 270, 1127 μm ±290, 920 μm ± 220). However for the depth of crypts, the phytogenic effect is found only at the level of the duodenum (238 μm ± 50 vs 245 μm ± 60). Statistically, there was no effect of the phytogenic products on the different parts of the broilers gut, in the experimental group at 42 days.